Jana (Januszka) Białostockiego do Vincenzów listy sztorcowe (1941–1945) - Jan Choroszy (Quart)
The Stanisław Vincenz Archive in the Manuscript Department of the Ossolineum Library houses an extensive collection of correspondence of Vincenzs with Jan Białostocki and his family, whose acquaintanceship began in 1925. Among the surviving letters are six scripts from 1941–1945, addressed to Stanisław Vincenz, a prose writer and essayist who was then living in Hungary after fleeing Poland in the spring of 1940. This epistolary dialogue – of which the second part remains unknown, as the letters of the author of On the High Uplands did not survive the Warsaw Uprising – captures Jan (Januszek) Białostocki’s reflections on his weariness with everyday life under occupation. He describes his efforts to overcome this sense of fatigue through a diverse range of studies (including methodology of science, logic, biology, classical philology, philosophy, art history, and aesthetics), as well as through reading, attempts at translating Dante, and practising wood engraving. This unique source material sheds new light on the childhood and adolescence of the eminent scholar, who was deeply influenced by Vincenz – both a sage and an erudite thinker. The transcription is preceded by an introduction and a brief editorial note, with the letters supplemented by essential contextual explanations.